A Modern Guide to National Urban Policies in Europe - Zimmermann, Karsten; Fedeli, Valeria (Elgar Modern Guides, 2021)
Written in a clear and concise style, this Modern Guide provide a timely overview and comparison of urban challenges and national urban policies in 13 European countries, addressing key issues such as housing, urban regeneration and climate change. A team of international contributors explore the gap between the rise of international urban agendas and variegated national urban policies, examining whether a more bespoke approach is better than the traditional 'one size fits all'.